2019
DOI: 10.1152/ajpheart.00686.2018
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular vortex and intraventricular pressure difference in dogs under various loading conditions

Abstract: Restrictions on the conventional evaluation of diastolic function have been recognized, especially under various loading conditions. Recently, new noninvasive ventricular vortex indexes have been introduced and are expected to reflect the cardiac function. Physiologically, there is a hypothesis that the intraventricular pressure difference (IVPD) is related to the formation of vortexes. IVPD and vortex indexes were simultaneously measured, and the relationship between the two was investigated. To verify the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 24 publications
3
19
1
Order By: Relevance
“…This suction force created by the pressure gradient from the left atrium to the LV apex is a major determinant of adequate filling in the early diastole during normal cardiac function [ 16 , 45 , 46 ]. The IVPG has been recognized as an index of diastolic function in early diastole [ 14 ]; however, in the present study, IVPG was decreased even though the diastolic function was preserved as indicated by the non-significant change in Tau and left ventricular end-diastolic pressure. At the beginning of relaxation, the energy stored in the LV wall during systole is released [ 47 ].…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…This suction force created by the pressure gradient from the left atrium to the LV apex is a major determinant of adequate filling in the early diastole during normal cardiac function [ 16 , 45 , 46 ]. The IVPG has been recognized as an index of diastolic function in early diastole [ 14 ]; however, in the present study, IVPG was decreased even though the diastolic function was preserved as indicated by the non-significant change in Tau and left ventricular end-diastolic pressure. At the beginning of relaxation, the energy stored in the LV wall during systole is released [ 47 ].…”
Section: Discussioncontrasting
confidence: 72%
“…The mid to apical-IVPG, which is the pressure difference between mid and apical parts, represents a suction force that is reported to reflect the active relaxation of the LV during diastole. Besides, Tau, which is the most established index to describe left ventricular diastolic function that obtained invasively by catheterization, showed a negative correlation with total-, basal-, and mid-IVPD values in an experimental canine model under different loading conditions [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vorticity can be obtained by intracardiac flow analysis using Vector Flow Mapping (VFM) or 4D-flow MRI 3,4 . Left ventricular vorticity during early diastolic phase reflect tau, which is the gold standard for measuring left ventricular relaxation property, independent from preload 5 . Another report showed that the vorticity related to clinical signs of diastolic dysfunction 5 .…”
mentioning
confidence: 99%
“…Left ventricular vorticity during early diastolic phase reflect tau, which is the gold standard for measuring left ventricular relaxation property, independent from preload 5 . Another report showed that the vorticity related to clinical signs of diastolic dysfunction 5 . These reports suggested vorticity have a potential of to be a novel marker of diastolic function.…”
mentioning
confidence: 99%
See 1 more Smart Citation